Large-scale evaluation of the suitability of buildings for photovoltaic integration: Case study in Greater Geneva. (15th June 2022) - Thebault, Martin; Desthieux, Gilles; Castello, Roberto; Berrah, Lamia
Abstract: In the context of a rapid and massive deployment or renewable energy and in particular solar photovoltaic, it is necessary to develop methods and tools to guide this deployment. To this end, this work proposes a multicriteria approach for evaluating the suitability of a building to be equipped with photovoltaic (PV) systems (PV suitability). In the present case, technical (roof complexity), economic (payback period), environmental (CO2 reduction), energetic (self-consumption), as well as social (heritage constraint) criteria are considered. These criteria are evaluated for each building of the Greater Geneva Agglomeration (GGA), a cross-border French–Swiss territory of nearly 270 000 buildings. A multicriteria method, ELECTRE TRI, makes it possible to sort these buildings into three categories, A, B, and C, that correspond to "very high, " "high, " and "moderate" PV suitabilities, respectively. Large differences are observed within the 210 municipalities of the GGA since some of them have almost no A-ranked buildings whereas others comprise more than 70% of these buildings. It is shown that, by prioritizing the A-ranked buildings, almost 50% of the annual electricity consumption of the Geneva Canton could be produced by PV systems. Finally, the method developed here offers a decision-aiding tool that could be used at a territory scale to achieve energy transition goals in terms of solar PV deployment. Highlights: Large-scale evaluation of the suitability of buildings to be equipped with photovoltaic systems (PV suitability). Simple labeling of PV suitability: A (very high), B (high), C (moderate). Multidisciplinary and multicriteria approaches considering social, economic, energetic, environmental, and technical criteria. A cross-border territory (data from two countries, three administrative regions, 270 000 buildings). Decision support for massive urban deployment of PV systems. Graphical abstract: